Effectiveness of forward freight agreements in mitigating handymax bulk ship-owners’ business risks between 2006 and 2015 - Tyan, Chwan Rong (2017)
As a shipowner, there are various methods to minimise their risk exposure in the highly volatile shipping market to ensure their continual survival. Traditionally, there is the hedging on the physical position by entering Time Charters (TC) to hedge on their earning. Presently, there is also the paper tool called Forward Freight Agreement (FFA) traded on the market for shipowners to hedge on their earning. The aim of this paper is to investigate which tool will be a more effective tool in mitigating the shipowner’s risk in the Handymax bulk market. Since due to the insufficient and inconsistent data of Handymax, this study will make use of the data from the Handysize market to simulate that of the Handymax The first part of this study discussed in depth about the types of risk faced by the shipowners and the correlation of the routes in the Handymax bulker market. Then the study further discussed the effectiveness of using FFA for trading in the spot market. Lastly, in this paper, there is a comparison the effectiveness of hedging using the traditional TC method and FFA in mitigating the shipowners’ business risk. Models are formulated to simulate the shipowner’s financial performance in term of acquiring and deploying the Handysize bulk carriers via TC using information available from Clarkson Intelligence Network, Bloomberg and Moore Stephens OpsCost. The time frame for this experiment is 10 years, from 2006 to 2015. The paper concluded that TC is actually a better hedging tool than FFA but the combine usage of both TC and FFA in different asset classes will be more effective in mitigating the shipowners’ business risk. The hypotheses of the paper have been proven to be valid.